BBC Proms 2014: Weir, Zhou and Rands. (2nd January 2015) - Miller, Malcolm
Abstract : Three new piano works premiered at the 2014 Proms showed an intriguing variety of styles and idioms in twenty-first-century music with varying levels of success. Paradoxically the more inventive piano techniques emerged in the more vividly characterised and communicative works by Judith Weir and Zhou Long, while Bernard Rands' neo-modernist concerto lacked a clear identity.